The Influence of Corruption, Trade Openness, Political Stability, and Skilled Labor on Foreign Direct Investment (FDI) in BRICS Countries - Erni Setyowati; Siti Aisyah (Majapahit Journal of Islamic Finance and Management, 2026)
Foreign direct investment flows play a crucial role in driving economic growth and development in developing countries, including the BRICS group. However, FDI inflows are inextricably linked to the economic and political conditions of each country. This study aims to determine the influence of corruption levels, trade openness, political stability, and skilled labor on foreign direct investment (FDI) flows into BRICS countries (Brazil, Russia, India, China, and South Africa) during the 2010-2020 period. The data used are secondary data obtained from the World Bank using panel data regression analysis. The results of this study indicate that corruption, trade openness, and labor have a significant negative effect on FDI. This leads to an increase in these factors, which in turn reduces foreign investment inflows into BRICS countries. Meanwhile, political stability has a significant positive effect on FDI, meaning that the more stable a country's political conditions, the greater the FDI inflows. Therefore, to increase investment attractiveness in the BRICS region, efforts are needed to strengthen political stability and improve the quality of institutions through reducing corruption, managing trade openness, and increasing labor productivity to remain cost-competitive.